Multigenerational workforce and organizational performance: A convergent analysis - Chilufya C. Chiwisa; Mubanga Mpundu (International Journal of Academe and Industry Research)
The composition of today's workforce has experienced a notable increase in age diversity with four generations working together. The purpose of the study was to explore the influence of a multigenerational workforce on organizational performance, specifically examining the skillsets of different generational cohorts. The motivation for doing the study arose from the necessity to comprehend the skill sets of various generational cohorts and how this understanding could assist firms in fostering an inclusive work environment and effectively manage the human capital of diverse generational groups. A convergent mixed study methodology was utilized to quantitatively define demographic parameters and qualitatively investigate concepts and themes of the phenomenon, as well as provide a comprehensive understanding of participant experiences. Data was collected from a purposively sampled population of 60 employees across three distinct generational cohorts: Baby Boomers, Generation X, and Generation Y and included 4 senior managers and 56 line employees from a selected school in Lusaka District in Zambia. The data was acquired through surveys, focus group discussions, and semi-structured interviews. The results indicated the presence of different generational skillsets within the workforce. The findings proposed strategies and best practices for managing a workforce consisting of multiple generations. Organizations can utilize the study's findings to enhance employee engagement within a multigenerational workplace. Furthermore, the data can be utilized to guide management methods to maintain harmonious working relationships.